The two-phase state of melt at continuous casting of the high carbon steel - Ju. A. Samojiovich; V. I. Timoshpolskij; N. V. Andrianov; I. A. Trusova; V. A. Matochkin (Литьë и металлургия)
There are given the results of calculation of the ingots crystal structure and continuously cast slugs indexes during the procedure of solidification (of the metal stay duration in two-phase state, of the dendritic nucleus size and medium size of iron sulfide), based on using of the experimental and theoretical methods.